TEORI KEPEMIMPINAN PENDIDIKAN (Studi Dasar Teori Sifat, Teori Perilaku, Dan Teori Situasional Dalam Kepemimpinan Pendidikan) - Pangestu, Prayogo; Asy'ari, Hasyim (Andragogi: Jurnal Pendidikan Islam dan Manajemen Pendidikan Islam, 2024)
This study examines three major leadership theories: Trait Theory, Behavioral Theory, and Situational Theory, as well as their application in educational management, particularly in the context of Islamic education. Trait Theory emphasizes the innate characteristics of a leader, Behavioral Theory focuses on behavioral patterns that can be learned, while Situational Theory highlights the importance of leadership flexibility in adapting leadership styles to specific conditions and situations. The analysis reveals that each theory has its own strengths and weaknesses, but the application of Situational Theory is considered the most effective as it allows leaders to adapt to the needs and challenges they encounter. This study also emphasizes the importance of integrating modern leadership theories with spiritual and moral values in Islamic education to make leadership more relevant and effective